Financial and economic mechanisms for ensuring the reintegration of war veterans in Ukraine (Economics and region, 2024)
The financial and economic mechanisms for the reintegration of war veterans in Ukraine represent a key aspect of ensuring this process, allowing veterans not only to return to civilian life but also to become active participants in economic and social activities. Since the number of veterans has significantly increased following the onset of the full-scale invasion, both governmental and non-governmental organizations face challenges in effectively implementing rehabilitation, reintegration, and veteran business support programs. The primary financial sources for veteran reintegration include centralized state resources, decentralized resources, and international aid. State programs encompass direct payments to veterans (both one-time and regular), benefits (such as utility subsidies, medical care, etc.), as well as professional and social adaptation programs, rehabilitation services, and access to sanatorium treatment. Funding for these purposes has substantially increased in recent years. However, audits reveal inefficiencies in the use of budgetary funds, including inadequate coordination between government agencies and the absence of clear reintegration strategies. Furthermore, rehabilitation and readaptation programs are poorly managed, creating obstacles for veterans in accessing the services promised. Among decentralized resources, the funds of non-governmental organizations, largely financed by international non-profit organizations, play a significant role. An important aspect of reintegration is the promotion of veterans' business activity. Government programs such as "eRobota" and grants from the Ukrainian Veterans Fund, alongside international grant programs, provide veterans with financial support for starting and developing their own businesses. The domestic financial sector contributes to the social and economic reintegration of veterans not only by offering loans under preferential conditions but also through initiatives aimed at improving financial literacy among veterans and their families and increasing the inclusiveness of financial services.
Keywords: veterans; socio-economic reintegration; financial resources; budget funds; grants; financial inclusion